1990
DOI: 10.1038/bjc.1990.13
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of misonidazole and cyclophosphamide on aerobic and hypoxic cells in a C3H mammary carcinoma in vivo

Abstract: Summary The chemosensitising effect of the nitroaromatic radiosensitiser misonidazole (MISO) on the alkylating agent cyclophosphamide (CTX) has been investigated in a C3H mammary carcinoma in CDF, mice.The selective cytotoxicity against aerobic and hypoxic cells was measured indirectly, using a local tumour control (TCD50) assay. The hypoxic fraction was calculated from the dose difference between the TCD50s for tumours irradiated either in air or under clamped conditions. The relative survival of tumour cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This DEF was defined as the ratio between the RDm values for radiation alone and when radiation was combined with cis-DDP. A comparison between the estimated RD50 was performed as described recently (Grau et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…This DEF was defined as the ratio between the RDm values for radiation alone and when radiation was combined with cis-DDP. A comparison between the estimated RD50 was performed as described recently (Grau et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the situation most similar to this is where misonidazole was combined with continuous (up to 18.5 hr) low-dose-rate irradiation in a mouse model, producing a radiosensitizing effect (Fu et al, 1980). It also resembles the use of misonidazole as a chemosensitizer, selectively sensitizing tumour cells to some cytotoxic drugs via both hypoxia-mediated mechanisms (inhibition of DNA repair or intracellular thiol depletion) and inhibition of hepatic drugmetabolizing enzymes (Twentyman and Workman, 1983;Grau et al, 1990). High tumour levels of misonidazole, obtained at the time of cytotoxic drug administration, continue throughout the active life of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious interpretation is that SR2508 (not a known myelotoxic agent) may potentiate the toxicity of cyclophosphamide to bone marrow stem cells. This may occur as a result of GSH depletion in oxic cells as occurred in peripheral mononuclear cells; enhanced toxicity of cyclophosphamide (Grau et al, 1990) and other alkylators (Durand & Chaplin, 1987;Horsmann et al, 1989) to oxic cells is welldescribed in vivo and in spheroids. Allalunis et al have shown in addition that a proportion of normal marrow cells exist in a hypoxic environment (Allalunis et al, 1983).…”
Section: Discussionmentioning
confidence: 99%